Impulsivity Markers in Parkinsonian Subthalamic Single‐Unit Activity. Issue 6 (16th January 2021) - Micheli, Federico; Vissani, Matteo; Pecchioli, Guido; Terenzi, Federica; Ramat, Silvia; Mazzoni, Alberto
ABSTRACT: Background: Impulsive‐compulsive behaviors are common in Parkinson's disease (PD) patients. However, the basal ganglia dysfunctions associated with high impulsivity have not been fully characterized. The objective of this study was to identify the features associated with impulsive‐compulsive behaviors in single neurons of the subthalamic nucleus (STN). Methods: We compared temporal and spectral features of 412 subthalamic neurons from 12 PD patients with impulsive‐compulsive behaviors and 330 neurons from 12 PD patients without. Single‐unit activities were extracted from exploratory microrecordings performed during deep brain stimulation (DBS) implant surgery in an OFF medication state. Results: Patients with impulsive‐compulsive behaviors displayed decreased firing frequency during bursts and a larger fraction of tonic neurons combined with weaker beta coherence. Information carried by these features led to the identification of patients with impulsive‐compulsive behaviors with an accuracy greater than 80%. Conclusions: Impulsive‐compulsive behaviors in PD patients are associated with decreased bursts in STN neurons in the OFF medication state. © 2021 International Parkinson and Movement Disorder Society